Assessing the Probability of Affirmative Action Women’s Quota for Members of the Regional Representative Council (DPD) (Jurnal Bina Praja, 2023)
Gender quota policies for women in parliament or politics worldwide have developed since the 1990s. Indonesia applies this policy to the House of Representatives (DPR) as a political representation with a 30 (thirty) percent quota. As a fellow national parliamentary institution that is part of the People's Consultative Assembly (MPR), it turns out that there is a policy vacuum for DPD institutions. The vacuum, in addition to illustrating discriminatory practices, can potentially result in a very minimal representation of women in the institution. This study aims to assess the probability of implementing a similar policy for DPD institutions or provide other recommendations that are more appropriate. This research used normative legal research that uses the statute approach, conceptual approach, and comparative approach. Our data is obtained from a literature study and will be analyzed qualitatively. The results of this study, based on the consideration of nomination inequality and patriarchal culture, comparison of other countries, DPD as part of the MPR, Indonesia's bicameral system, and the correlation of Regional Representation and Women's Issues in Indonesia; DPD has several important and relevant arguments for implementing affirmative gender quota policy. However, against these considerations, there are also arguments that are not important and irrelevant, have no significant impact, or are impossible to apply, which is a challenge to implement affirmative policies such as DPR. Therefore, the most appropriate recommendation for DPD is simply through more massive socialization of candidacy by the General Election Commission (KPU) so that the legal culture in the form of awareness of the existence of female DPD members will grow and concerns about the lack of female DPD members can be prevented.
Keywords: gender; DPD; affirmative action